2017
DOI: 10.5897/ajps2016.1502
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterotic orientation of mid-altitude sub-humid tropical maize inbred lines for grain yield and related traits

Abstract: Information on the combining ability and heterotic pattern of elite inbred lines is essential to maximize their use in hybrid maize development. This study was conducted to determine combining ability and heterotic pattern of locally developed maize inbred lines for grain yield and related traits. Seventeen inbred lines (10 female inbred lines and 7 tester inbred lines) were used to generate 70 single cross hybrids using line by tester crossing scheme. The resulting 70 cross progenies plus two standard checks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
(10 reference statements)
11
12
0
1
Order By: Relevance
“…In line with the present results (Melkamu, 2013). Shushay et al (2013) and Tolera et al (2017) found significantly positive and negative SCA effects for plant and ear height.…”
Section: Estimates Of Specific Combining Ability Effectsmentioning
confidence: 95%
“…In line with the present results (Melkamu, 2013). Shushay et al (2013) and Tolera et al (2017) found significantly positive and negative SCA effects for plant and ear height.…”
Section: Estimates Of Specific Combining Ability Effectsmentioning
confidence: 95%
“…Heterosis and trait association has been studied in Ethiopia for different sets of new maize inbred lines (Dagne et al, 2007;Worku et al, 2008;Girma et al, 2015 andTolera et al, 2017). Highland maize breeding program at Ambo Agricultural Research Center (AARC) in collaboration with CIMMYT recently developed crosses whose standard heterosis has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, SCA refers to cases in which some hybrid combinations perform comparatively better or less than expected based on the average performance of the parental lines involved. GCA and SCA effects are important indicators of the level of usefulness of the inbred lines in hybrid combinations and in categorizing materials into heterotic groups (Tolera et al, 2017). Combining ability analysis and collection of correct genetic information in breeding materials is necessary at the beginning of the development of the inbred line.…”
Section: Introductionmentioning
confidence: 99%
“…Details of combining ability of maize germplasm are necessary for maximizing the benefits of hybrid development. Many researchers have reported on the combining ability and heterosis for maize grain yield (Dagne, 2008;Berhanu et al, 2009, Amiruzzaman et al, 2011Abuali et al, 2012;Mohammad et al, 2016;Dar et al, 2017;Tolera et al, 2017;Tulu et al, 2018). Combining ability analysis can be very useful if properly conducted and the results are correctly interpreted.…”
Section: Introductionmentioning
confidence: 99%